In an arithmetic sequence, every pair of consecutive terms differs by a fixed number c, so that the n-th term [tex]a_n[/tex] is given recursively by
[tex]a_n=a_{n-1}+c[/tex]
Then for n ≥ 2, we have
[tex]a_2=a_1+c[/tex]
[tex]a_3=a_2+c = (a_1+c)+c = a_1 + 2c[/tex]
[tex]a_4=a_3+c = (a_1 + 2c) + c = a_1 + 3c[/tex]
and so on, up to
[tex]a_n=a_1+(n-1)c[/tex]
Given that [tex]a_3=126[/tex] and [tex]a_{64}=3725[/tex], we can solve for [tex]a_1[/tex]:
[tex]\begin{cases}a_1+2c=126\\a_1+63c=3725\end{cases}[/tex]
[tex]\implies(a_1+63c)-(a_1+2c)=3725-126[/tex]
[tex]\implies 61c = 3599[/tex]
[tex]\implies c=59[/tex]
[tex]\implies a_1+2\times59=126[/tex]
[tex]\implies a_1+118 = 126[/tex]
[tex]\implies \boxed{a_1=8}[/tex]